Maternal Response to Child Affect: Role of Maternal Depression and Relationship Quality - Morgan, Judith K. (J Affect Disord, 2015)
BACKGROUND: Maternal depression is associated with negative outcomes for offspring, including increased incidence of child psychopathology. Quality of mother-child relationships can be compromised among affectively ill dyads, such as those characterized by maternal depression and child psychopathology, and negatively impact outcomes bidirectionally. Little is known about the neural mechanisms that may modulate depressed mothers’ responses to their psychiatrically ill children during middle childhood and adolescence, partially because of a need for ecologically valid personally relevant fMRI tasks that might most effectively elicit these neural mechanisms. METHODS: The current project evaluated maternal response to child positive and negative affective video clips in 19 depressed mothers with psychiatrically ill offspring using a novel fMRI task. RESULTS: The task elicited activation in the ventral striatum when mothers viewed positive clips and insula when mothers viewed negative clips of their own (versus unfamiliar) children. Both types of clips elicited activation in regions associated with affect regulation and self-related and social processing. Greater lifetime number of depressive episodes, comorbid anxiety, and poor mother-child relationship quality all emerged as predictors of maternal response to child affect. LIMITATIONS: Findings may be specific to dyads with psychiatrically ill children. CONCLUSIONS: Altered neural response to child affect may be an important characteristic of chronic maternal depression and may impact mother-child relationships negatively. Existing interventions for depression may be improved by helping mothers respond to their children’s affect more adaptively.